1986
DOI: 10.1139/z86-005
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and postglacial dispersal of freshwater fishes of Labrador

Abstract: The voluminous literature on the freshwater and diadromous fishes of Labrador is summarized in distributional maps. A total of 25 obligate freshwater spawning and one catadromous species has been reported. Fishes from Atlantic and Mississippi refugia probably invaded the region from the Great Lakes basin primarily via glacial Lake Barlow-Ojibway, crossing Quebec north of the Otish Mountain to the headwaters of the Churchill River system. Additional dispersal routes existed to the north and south. Euryhaline sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 10 publications
4
43
0
Order By: Relevance
“…Many of the freshwater fish migrated into the lower Churchill River water− shed from the west as glaciers retreated. Species such as salmonids may have ex− tended into the river from the east (Black et al 1986). Some wildlife (e.g., moose) colonized the area along corridors created by natural changes in the landscape or as a result of human activity.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the freshwater fish migrated into the lower Churchill River water− shed from the west as glaciers retreated. Species such as salmonids may have ex− tended into the river from the east (Black et al 1986). Some wildlife (e.g., moose) colonized the area along corridors created by natural changes in the landscape or as a result of human activity.…”
Section: Introductionmentioning
confidence: 99%
“…1) was therefore impossible before this time. Eurhyaline fishes, such as brook charr, most likely took advantage of their physiological tolerance to saltwater to reinvade previously ice-covered areas via coastal dispersal (Black et al 1986). Thus, given the relatively short evolutionary time since the postglacial settlement of brook charr populations, we tested the hypothesis that the patterns of genetic differentiation among brook charr from different drainages still reflect the sequence of successive founding events from one river drainage to another.…”
mentioning
confidence: 99%
“…Previous authors have postulated that brook trout from the Atlantic and Mississippian refugia migrated through Québec to recolonize Labrador, whereas the Atlantic refugium alone was the source for fish invading coastal regions (Black et al, 1986). Conversely, Danzmann et al (1998) have suggested that northeastern brook trout populations may have been founded by fish from an Acadian refugium.…”
Section: Inferences About Postglacial Recolonization Historymentioning
confidence: 99%
“…One possible scenario for the colonization of Labrador by brook trout is that fish from the Atlantic and Mississippian refugia dispersed through Québec and into Labrador, whereas other fish from the Atlantic refugium invaded coastal regions (Black et al, 1986). To determine the refugial origins and specific routes of postglacial recolonization of brook trout in the northern extreme of their natural range, we examined 1960-bp mtDNA sequences representing 126 fish from seven regions in eastern Canada, most extensively in Labrador.…”
Section: Introductionmentioning
confidence: 99%